THE CYTOKINES SYNTHESIS IN VITRO IN THE TICK-BORNE ENCEPHALITIS VIRUS INFECTED CELLS AND IN THE PRESENCE OF INACTIVATED VACCINE - M. V. Mesentseva; I. F. Аntoshina; O. V. Мorozova (Инфекция и иммунитет, 2014)
Abstract. Tick-borne encephalitis (TBE) is severe neuroinfectious disease with involvement of immune mechanisms in pathogenesis. Comparative analysis of synthesis of key cytokines had been performed for the TBE virus (TBEV) infected cells and in the presence of inactivated vaccine against TBE in vitro. Persistent TBEV infection of immortal tissue culture of human larynx cancer cells caused transcription activation of interferons IFNα, IFNγ, IFNλ1, interleukins IL-1β, IL-2, IL-4, IL-8, IL-10, IL-12, tumour necrosis factor TNFα as well as one of apoptosis factors Fas. Comparison of transcription and production of cytokines revealed that the TBEV infection resulted in posttranscription Th1 shift of cytokine response. In the presence of inactivated vaccine against TBE based on the same strain Sofjin of the TBEV activation of transcription of cytokines IFNα, IFNλ1, IL-4, IL-10 was also observed as after the TBEV infection that together with an additional stimulation of GM-CSF production might serve as an evidence of Th2 response. Involvement of IFNIII type (IFNλ1) both during persistent infection and after addition of inactivated vaccines was found in the first time. Differences in dynamics of cytokines IL-2, IL-8, IL-10, IL-12, TNFα response during the TBEV infection and in the presence of inactivated vaccine are described.